Down-regulation of T-type Cav3.2 channels by hyperpolarization-activated cyclic nucleotide-gated channel 1 (HCN1): Evidence of a signaling complex. Issue 5 (3rd September 2017) - Fan, Jing; Gandini, Maria A.; Zhang, Fang-Xiong; Chen, Lina; Souza, Ivana A.; Zamponi, Gerald W.
ABSTRACT: Formation of complexes between ion channels is important for signal processing in the brain. Here we investigate the biochemical and biophysical interactions between HCN1 channels and Cav3.2 T-type channels. We found that HCN1 co-immunoprecipitated with Cav3.2 from lysates of either mouse brain or tsA-201 cells, with the HCN1 N-terminus associating with the Cav3.2 N-terminus. Cav3.2 channel activity appeared to be functionally regulated by HCN1. The expression of HCN1 induced a decrease in Cav3.2 Ba 2+ influx ( I Ba 2+ ) along with altered channel kinetics and a depolarizing shift in activation gating. However, a reciprocal regulation of HCN1 by Cav3.2 was not observed. This study highlights a regulatory role of HCN1 on Cav3.2 voltage-dependent properties, which are expected to affect physiologic functions such as synaptic transmission and cellular excitability.